Growth Performance and Nutritional Analysis of Spirulina platensis in Different Concentrations of Papaya Skin Powder Media - Toyub, MA; Uddin, MZ; Miah, MI; Habib, MAB (Bangladesh Journal of Scientific and Industrial Research, 2011)
The growth performance of Spirulina platensis was studied in four different concentrations viz. 0.3, 0.4, 0.5 and 0.6 g/l of papaya (Carica papaya) skin powder media (PSPM) and in control, Kosaric Medium (KM) in triplicate. The initial cell weight of S. platensis was 6.0 mg/l which attained a maximum weight of 913.13 mg/l on the 10th day of culture in the control KM followed by 699.07, 612.13, 538.99 and 377.48 mg/l that grown in 0.40, 0.30, 0.50 and 0.60 g/l of PSPM respectively. Similar trend was observed in the case of chlorophyll a content ranging 3.57 to 8.15 mg/l. The specific growth rate (SGR, μ/day) of S. platensis on the basis of cell weight and chlorophyll a content was recorded in the ranges of 0.41 to 0.50 and 0.41 to 0.49, respectively, for all the treatments. The SGR on the basis of cell weight and chlorophyll a was recorded significantly (p<0.05) higher in KM among all the treatments. On the other hand among the four different concentrations of PSPM, 0.40 g/l showed significantly (p<0.05) higher SGR than others. The pH and other physico-chemical factors were within suitable range of algae culture. The cultured microalga was nutritionally rich. Keywords: Spirulina; Papaya skin; Cell weight ; Chlorophyll a DOI: http://dx.doi.org/10.3329/bjsir.v46i3.9039 BJSIR 2011; 46(3): 333-338